THE EFFECTIVENESS OF MEDIATION IN RESOLVING LAND DISPUTES IN INDONESIA AND MALAYSIA: EFEKTIVITAS MEDIASI DALAM PENYELESAIAN SENGKETA PERTANAHAN DI INDONESIA DAN MALAYSIA - VERI SURYA WIJAYA, YOGA (ADHAPER: Jurnal Hukum Acara Perdata, 2025)
This study analyzes the effectiveness of mediation in resolving land disputes in Indonesia and Malaysia through a comparative approach. The scope of the study encompasses: (1) the mechanisms and legal basis of land dispute mediation in Indonesia; (2) the mechanisms and legal basis in Malaysia; and (3) the similarities, differences, and determinants of mediation success in both countries. Employing a normative-juridical method supported by secondary empirical data including institutional reports, case records, and official publications the analysis examines mediation stages, mediator roles, dispute scope, and the binding force of agreements. The findings indicate that mediation effectiveness is significantly influenced by institutional design, mediator competence, transparency of land data, certainty of rights status, and party compliance. Furthermore, this study presents a tabulation of success and failure rates over the past five years to observe resolution trends. Comparative findings confirm that procedural harmonization, enhanced mediation quality, and strengthened enforcement of agreements are pivotal for achieving expeditious, cost-effective, and equitable dispute resolution. This research serves as a strategic reference for policymakers and practitioners in strengthening mediation as an alternative dispute resolution mechanism in the region.